A primary intracranial neuroepithelial neoplasm with novel TCF3::BEND2 fusion: a case report - Linmao Zheng; Tao Luo; Jie Xian; Mengxin Zhang; Xiuyi Pan; Xiang Wang; Qiang Yue; Qiao Zhou; Ni Chen (Acta Neuropathologica Communications)
Abstract Astroblastoma, MN1-altered, is a rare circumscribed glial neoplasm that is composed of round, cuboidal, orcolumnar cells with astroblastic perivascular pseudorosettes, often associated with MN1::BEND2 and MN1::CXXC5 fusions. Atroblastoma-like gliomas harbouring EWSR1::BEND2 have been reported that they defined an epigenetically distinct subtype of astroblastoma. We report a case of a 19-year-old female with an intracranial neuroepithelial tumor featuring a novel TCF3::BEND2 fusion. This tumor, while classified as EWSR1::BEND2 gliomas based on DNA methylation, did not exhibit the MN1 alteration or typical astroblastoma morphology. The patient, initially diagnosed as ependymoma WHO grade 2 following surgery for an intracranial tumor four years prior, presented with a suspected recurrence. Magnetic resonance imaging identified a mixed solid-cystic lesion in the temporal area of the left lateral ventricle. For the recurrent tumor, the histological examination revealed the tumor cells predominantly exhibited a solid arrangement, with the solid areas primarily consisting of oval and short-spindle cells. In certain regions, loosely arranged short-spindle cells was observed. The tumor exhibited high cellular density, nuclear atypia, and frequent mitoses, but lacked the hallmark features typically associated with astroblastoma. Immunohistochemistry revealed patchy positivity for GFAP and OLIG2, diffuse positivity for EMA, and a high MIB-1 labeling index. Genome-wide DNA methylation profiling confirmed the tumor’s classification as EWSR1::BEND2 gliomas with a high-confidence match and revealed focal deletion of chromosome 9q. Targeted next-generation sequencing identified a TCF3::BEND2 fusion, validated by reverse transcription polymerase chain reaction and Sanger sequencing. This case broadens the genetic spectrum of high-grade neuroepithelial tumor and suggests that BEND2 alterations may serve as critical determinants for this EWSR1::BEND2 glioma subgroup within the methylation classifier.